Temporal diversity patterns for fungi and mites associated with decaying Sporobolus pumilus (Spartina patens) in the Minas Basin, Nova Scotia - Bruce Malloch; Gavin Kernaghan; Allison K. Walker (Canadian Science Publishing, 2022)
Coastal salt marshes provide many ecosystem services; however, little is known of the biology of decomposer taxa in these systems. This study employed aboveground and belowground litterbags to characterize the fungal and mite communities associated with the dominant salt marsh grass, Sporobolus pumilus, in the Minas Basin, Nova Scotia. Decomposition rates of aboveground and belowground tissues and environmental variables were quantified to contextualize temporal patterns in community composition. Aboveground litterbag mass loss peaked in July and decreased consistently over succeeding months, which positively correlated with fungal richness. Fungal and mite richness displayed inverse relationships over time, with mites gradually increasing in diversity before peaking in November, suggesting the presence of a complex detrital network where mites and fungi respond to different and possibly unrelated environmental cues. This study offers a first look at temporal community dynamics of two neglected groups of decomposers associated with S. pumilus in Canada.